Enhancing Vocational School Graduates' Work Readiness through Principal Leadership Strategies: A SWOT Analysis Approach - Hendri Jaya Putra; Mohzana; Musifuddin (Al-Qalam Institue, 2026)
This study aims to analyze the principal's leadership strategy based on SWOT analysis to improve the work readiness of vocational high school graduates. A qualitative case study design was employed, with data collected through in-depth interviews, observations, and documentation involving the principal, teachers, school management, industry partners, and alumni. Data were analyzed using Miles and Huberman's model, including data reduction, data display, and conclusion drawing. The findings indicate that the school's strengths lie in transformational leadership, industrial-based learning through internships, and the development of students' work culture. However, weaknesses in students' technical competencies and limited facilities were identified. External opportunities include industry partnerships and government support, while threats involve limited job availability and a mismatch between graduates' competencies and labor market demands. The SWOT-based leadership strategy adopted by the principal proves effective in enhancing soft skills, but less so in improving technical skills. This study contributes to the development of a strategic leadership model in vocational education, particularly in resource-constrained contexts, and emphasizes the importance of aligning school programs with industry needs.